Analysis of DS-CDMA system supporting heterogeneous traffic with decorrelating detector. - Zhiwei Mao (IEEE Transactions on wireless communications)
Single-cell and multiple-cell direct-sequence code-division multiple-access (DS-CDMA) systems supporting heterogeneous traffic are investigated when decorrelating detector is used at receiver. Theoretical analyses and numerical examples are presented to study the effect of imperfect power control on the system performance of the reverse link. As to the forward link, the system performance is analyzed and the power allocation problem at base stations is formulated as a constrained optimization problem. Two algorithms, namely, the optimal algorithm and the unit transmission power allocation (UTXPA) algorithm, are proposed to solve this optimization problem. Computer simulations are presented to compare the performance of the proposed algorithms.